Aerodynamic measures of speech in unilateral vocal fold paralysis (UVFP) patients. (April 2013) - Pinho, Cátia M. R.; Jesus, Luis M. T.; Barney, Anna
Abstract This paper reports the recording and analysis of an aerodynamic database of 51 words produced by four patients with unilateral vocal fold paralysis. The vowel–fricative–vowel boundaries were manually annotated, and the mean absolute oral airflow amplitude (OA), fundamental frequency (f0), and first formant intensity (IF1) were extracted from a 20 ms window in the steady state of each phone. A case study approach to analysis of phonatory behaviour for the subjects is presented. Significant differences were found between the absolute OA and IF1 for different phones. Large between-subject variations in absolute measures for OA and f0 were found. Relative values calculated from the difference in these parameters between phones show consistency for subjects of the same gender.